SIKLUS HIDUP (LIFECYCLE) PADA EKOWISATA BUKIT CEMENG SIDEMBUNUT BANGLI - I Gusti Ketut Indra Pranata Darma; I Wayan Wiwin; Ni Made Rai Kristina (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
Bukit Cemeng ecotourism has an interesting attraction related to nature and interesting photo spots. As one of the ecotourism destinations in Bangli, Bukit Cemeng faces challenges from the beginning to the present, which are related to the pandemic. In the life cycle of a tourist destination, there are phases starting from the exploration phase, community involvement, development to the decline and rejuvenation phase. This study uses a descriptive qualitative method with the researcher as the main instrument conducting research in the field and observing. The research data was carried out by direct interviews with the Bukit Cemeng Ecotourism manager, literature review and primary data search. The research data is based on literature studies from books, journal articles related to the Destination life cycle. Research activities were carried out in 2021 and were continued in April to June 2022. The expected results of this activity are related to the fulfillment of the life cycle of tourist destinations, the time period for each phase is fulfilled in Bukit Cemeng Ecotourism, especially when this research occurs. In addition to fulfilling the life cycle, this research to obtain alternative strategies for ecotourism in dealing with current conditions. Such as the strategy of making a jogging track as an additional attraction for Bukit Cemeng ecotourism.